The relationship between corporate social responsibility (CSR) and employee commitment among academic staff in UiTM Jengka Pahang / Nurfatin Nabihah Mohamed Yusof - Mohamed Yusof, Nurfatin Nabihah (Faculty of Business and Management, 2018)
Corporate Social Responsibility (CSR) is dependable to be implementing in the organization. The analysis shows the good impact which is CSR can give a positive effect to employee's commitment. The purpose of this study is to discover the relationship between Corporate Social Responsibility and Employee Commitment. There are many factors that can give to employee commitment such as leadership and reward to the employees. Researcher used the descriptive statistics and correlation analysis to investigate the effect of CSR towards Employee Commitment. In order to get the result, researcher distributed the questionnaire to employees of Academic Department in UiTM Jengka, Pahang. The questionnaire consists of three sections which are section A about demographic, section B about independent variable and section C about dependent variable. Researcher using Statistical Packages for Social Science (SPSS), version 2.0 in order to analysis the data and the result had found that CSR give a positive impact to employee commitment. The researcher used descriptive statistics to measure mean of Corporate Social Responsibility and Employee Commitment while correlations to determine the relationship between CSR and Employee Commitment.